ANALISIS PERHITUNGAN PAJAK PENGHASILAN BADAN PASAL 25 PADA PT WIJAYA RATNA ABADI - Indah Ayu; Rola Manjaleni (Jurnal Akuntansi dan Bisnis, 2026)
The problem is that company including several costs that cannot be deducted from taxable income based on tax regulations, namely donation costs, entertainment costs, and in-kind costs. The purpose of this study is to determine whether the income tax calculations carried out by PT Wijaya Ratna Abadi are in accordance with applicable tax regulations. The types and sources of data used in this study are primary data and secondary data with data collection techniques through interviews and document collection. From the results of the research and discussion that have been conducted, it can be concluded that PT Wijaya Ratna Abadi has not implemented income tax calculations in accordance with the provisions of the Tax Law.